Contribution of Tc-99m RBC SPECT/ CT in Intrahepatic and Peritoneal Splenosis Mimicking Malignancy - Kevser Oksuzoglu; Rabia Ergelen; Tunc Ones; Sabahat Inanir; Tanju Yusuf Erdil (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2017)
Splenosis is the autoimplantation of ectopic spleen tissue resulting heterotopic auto-transplantation and implantation of splenic tissue after splenic ruptur caused by trauma or splenectomy. It is a benign condition that often mimics malignancy in healthy patients or peritoneal metastases in cancer patients. We report a case of diffuse peritoneal splenosis mimicking neoplastic lesions.